Factors influencing histoplasmosis incidence in multidrug-resistant pulmonary tuberculosis patients: A cross-sectional study in Indonesia - Khairunnisa, Selfi; Soeroso, Noni N.; Abdullah, Muntasir; Siahaan, Lambok; Eyanoer, Putri C.; Daulay, Elvita R.; Wahyuningsih, Retno; Denning, David W. (Narra J, 2023)
Histoplasmosis is an infectious disease caused by the dimorphic fungus Histoplasma capsulatum, which, in chronic conditions, is generally difficult to distinguish from pulmonary tuberculosis based on its clinical appearance; therefore, diagnostic errors can occur. Meanwhile, the prevalence of multidrug-resistant pulmonary tuberculosis (MDR-TB) in Indonesia remains high. Study determining the incidence of histoplasmosis in MDR-TB is unavailable worldwide. The aim of this study was to determine the risk factors of histoplasmosis incidence in MDR-TB patients in Indonesia. A cross-sectional was conducted at H. Adam Malik General Hospital, Medan, Indonesia and the ELISA platform (semi-quantitative) was used to detect histoplasma antibodies. Factors associated with histoplasmosis incidence among MDR-TB were determined using a Chi-squared test. A total of 50 MDR-TB patients were included this study of which 14 of them (28%) had histoplasmosis. The majority of histoplasmosis occurred in males, in MDR-TB patients with a history of TB treatment and among who had chest x-rays with far-advanced lesions. However, statistical analyses indicated none of those factors (sex, TB treatment history, status of the lung) as well as age group, acid-fast bacillus result, Mycobacterium tuberculosis culture result, having pet, living in damp house, working in the field or plantation, having HIV infection and smoking status were associated with histoplasmosis incidence. This study highlights that the incidence of histoplasmosis is relatively high and therefore further studies are important to be conducted in Indonesia that has a high MDR-TB cases.